Myeloid-intrinsic cell cycle-related kinase drives immunosuppression to promote tumorigenesis - Zhou, Jingying (2023)
Massive expansion of immature and suppressive myeloid cells is a common feature of malignant solid tumors. Over-expression of cyclin-dependent kinase 20, also known as cell cycle-related kinase (CCRK), in hepatocellular carcinoma (HCC) correlates with reduced patient survival and low immunotherapy responsiveness. Beyond tumor-intrinsic oncogenicity, here we demonstrated that CCRK is upregulated in myeloid cells in tumor-bearing mice and in patients with HCC. Intratumoral injection of Ccrk-knockdown myeloid-derived suppressor cells (MDSCs) increased tumor-infiltrating CD8+T cells and suppressed HCC tumorigenicity. Using an indel mutant transgenic model, we showed that Ccrk inactivation in myeloid cells conferred a mature phenotype with elevated IL-12 production, driving Th1 responses and CD8+T cell cytotoxicity to reduce orthotopic tumor growth and prolong survival. Mechanistically, CCRK activates STAT3/E4BP4 signaling in MDSCs to acquire immunosuppressive activity through transcriptional IL-10 induction and IL-12 suppression. Taken together, our findings unravel mechanistic insights into MDSC-mediated immunosuppression and offer a therapeutic kinase-target for cancer immunotherapy.